Creating a global identity and collapsing local identities – example of Premiership - Ema Špehar; Jelena Lončar (Geoadria, 2022)
The subject of research and the purpose of this paper is to determine the effects of globalization on identity change within one of the most popular sports today, football. In order to avoid generalizations in the analysis, the English Premiership, one of the most famous football leagues, was chosen as a case study. The theoretical framework of the research is related to the identification of local changes under the influence of the global process, predominantly social and political. The time research covers the period from the creation of the Premiership, i.e. from 1992 until today. The research on selected globalization influences on the League’s development will try to clarify social changes resulting from the interaction of two main geographical segments - space and people. With the help of selected economic and financial indicators, the change of the local identity of the League, which was present in the past, into an increasingly pronounced global identity will be presented. In conclusion, it was found that the mentioned football league is an excellent example of the growing impact of the globalization process on sports, especially when it comes to world-famous football.